Distance education students' satisfaction: Do work and family roles matter?. Issue 1 (2nd January 2022) - Waterhouse, Philippa; Samra, Rajvinder; Lucassen, Mathijs
Abstract: The perceived flexibility of distance education, whereby students can juggle their multiple life roles, is often cited as the predominant reason for enrolling in this mode of study. Nonetheless, for distance learners their multiple roles often have a significant impact on their study experience. This study had three objectives: (1) to explore whether the paid worker role or family role predict distance learners' satisfaction; (2) to examine the relationship between role conflict and role facilitation regarding distance learners' satisfaction; and (3) to investigate the role of sociodemographic characteristics as potential moderators in this relationship. The analyses drew on data from 318 online distance learners. Students who reported living with children were less likely to report satisfaction with their educational experience, even after controlling for sociodemographic characteristics. The experience of role conflict and role facilitation was significantly associated with student satisfaction, although patterns differed according to students' prior educational attainment.